Development of a yz scan system for the improvement of an automatic system of radioactive seed implants in prostate brachytherapy (Brazilian Journal of Radiation Sciences, 2021)
Brachytherapy is the use of radiotherapy with insertion of radiation sources close to the site that needs treatment. It has become an extremely sought-after option by research fields for its impressive efficiency and practicality. In addition to being a fast-paced procedure, it allows patients to leave hospital care very soon after it is done, without pain or with minor discomfort, which can be considered an advantage.The brachytherapy procedure is divided into two stages, obtaining images of the region where seed implantation will take place and the application itself.  The images are obtained by ultrasonography, which will guide the insertion of the needle into the patient's body.  During the injection, the patient is anesthetized and immobilized, so that movements that compromise the accuracy of the needle, which, by the current manual method, are already subject to oscillations are avoided.Currently the application of radioactive seeds is done manually by a clinician who uses needles and monitors their positions through the images generated by ultrasound equipment. Thus, the main objective of this project was to improve the prototype of the Prostate Seed Implantation System (SISP), developed by the Nuclear Engineering Department of the UFMG (Nuclear Engineering Department).  Thus, the device allows automated scanning on x, y and z axes, facilitating the application of radioactive seeds in prostate brachytherapy treatments, which in current treatments are done manually by the clinician. And the possibility of controlling this movement via BLUETOOTH technology.
Keywords: Brachytherapy; implant automatic systems; radioactive seeds.